PENGARUH SEKTOR PARIWISATA DAN RETRIBUSI DAERAH TERHADAP PAD DAN PENYERAPAN TENAGA KERJA KABUPATEN/KOTA PROVINSI BALI - Fernanda, I Putu Ricky Mahesa; Dewi, Ni Putu Martini (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 10 No 3 (2021): VOL 10 NO 3,MARETI 2021 [ 899 - 1330], 2021)
The tourism sector is industry always experiencing development, so that it can increase employment. The research objective (1) analyze influence of tourism sector and local fees on PAD districts / cities Bali Province. (2) analyze influence of tourism sector, regional levies and PAD on absorption of labor districts / cities Bali Province. (3) analyze PAD mediates influence of tourism sector, regional levies and local revenue in districts / cities Bali Province. The method used non-participant, with path analysis and secondary data. The results this study indicate the tourism sector has positive and insignificant effect on PAD in the Regency / City Bali Province, while the local levies don’t have significant positive effect on local income in Regency / City of Bali Province. The tourism sector and PAD have significant positive effect on employment in Regency / City of Bali Province, while the local levy no significant positive effect on labor absorption in the Regency / City Bali Province. PAD partially mediates the effect of local user fees on labor absorption, while PAD doesn’t partially mediate the influence of tourism sector on labor absorption in Regency / City Bali Province.   Keywords: Tourism Sector, Regional Retribution, Original Local Revenue, Labor Absorption